Commercialism, Holism, and Individual Responsibility; Comment on "Buying Health: The Costs of Commercialism and an Alternative Philosophy" - Berit Bringedal (Kerman University of Medical Sciences, 2013)
Churchill and Churchill's editorial discusses negative (health) effects of commercialism in the provision of health care and nutrition. Three parts of their argument are commented: the claim that the fundamental problem of markets is the decomposition of the whole into parts ("reductionism"); the call for individual responsibility; and the notion of holism. On the three aspects the commentary concludes thus: Because provision of health and food must be controlled and managed in some form, an alternative to some kind of decomposition is hard to see. The call for individual responsibility is controversial due to its lack of attention to socioeconomic inequalities. The concept of "holism" is problematic due to its epistemological and normative status.